2019
DOI: 10.1111/jcmm.14505
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinic acid suppresses sebaceous lipogenesis of human sebocytes via activating hydroxycarboxylic acid receptor 2 (HCA2)

Abstract: Nicotinic acid (NA) activates hydroxycarboxylic acid receptor 2 (HCA2), and it is widely used in treating dyslipidaemias. Since its side effects include skin dryness, whereas its deficiency can be accompanied by dyssebacia, characterized by sebaceous gland enlargement, we asked if HCA2 is expressed on human sebocytes, and if NA influences sebocyte functions. By using human immortalized SZ95 sebocytes, we found that non‐cytotoxic (≤100 μmol/L; MTT‐assay) concentrations of NA had no effect on the homeostatic seb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 56 publications
1
25
0
1
Order By: Relevance
“…These data suggested that, similar to the classical eCBs (Dobrosi et al, 2008;Zákány et al, 2018), OEA is also able to promote differentiation of human sebocytes. Lipogenic potential of OEA was comparable to the ones typically seen in case of classical eCBs (e.g., AEA [30 mM]), arachidonic acid (50 mM), or the combination of linoleic acid and testosterone (100 mM and 1 mM, respectively, 48-hour treatments; Figure 1d) (Dobrosi et al, 2008;Géczy et al, 2012;Makrantonaki and Zouboulis, 2007;Markovics et al, 2019;Oláh et al, 2016b;Oláh et al, 2014;Szántó et al, 2019;Tó th et al, 2009;Zákány et al, 2018).…”
Section: Oea Promotes Differentiation Of Human Sebocytessupporting
confidence: 65%
See 2 more Smart Citations
“…These data suggested that, similar to the classical eCBs (Dobrosi et al, 2008;Zákány et al, 2018), OEA is also able to promote differentiation of human sebocytes. Lipogenic potential of OEA was comparable to the ones typically seen in case of classical eCBs (e.g., AEA [30 mM]), arachidonic acid (50 mM), or the combination of linoleic acid and testosterone (100 mM and 1 mM, respectively, 48-hour treatments; Figure 1d) (Dobrosi et al, 2008;Géczy et al, 2012;Makrantonaki and Zouboulis, 2007;Markovics et al, 2019;Oláh et al, 2016b;Oláh et al, 2014;Szántó et al, 2019;Tó th et al, 2009;Zákány et al, 2018).…”
Section: Oea Promotes Differentiation Of Human Sebocytessupporting
confidence: 65%
“…Detailed descriptions of the methods to assess sebaceous lipogenesis (Nile Red), differentiation-associated granulation (flow cytometry), viability (MTT assay), cell death (DilC 1 (5)-SYTOX Green labeling), proliferation (CyQUANT assay), Ca 2þ homeostasis (Fluo-4 AMebased fluorescent Ca 2þ -measurement), gene expression at the mRNA (Q-PCR) and protein levels (western blot, immunohistochemistry, and ELISA), and small interfering RNAemediated silencing can be found in our previous publications (Lisztes et al, 2019;Markovics et al, 2019;Oláh et al, 2017a;Oláh et al, 2016a;Oláh et al, 2014;Ramot et al, 2018;Szabó et al, 2020) and in the Supplementary Materials and Methods.…”
Section: Ethical Approvalmentioning
confidence: 95%
See 1 more Smart Citation
“…An important sign in the onset of acne lesions is that the hair follicle sebaceous gland unit can induce inflammation (Zouboulis, 2004) and is always accompanied by inflammatory responses during acne (Roodsari et al, 2010). IL-1α, IL-6 and TNF-α are the major cytokines of inflammation in the body, which can stimulate the proliferation and sebum production of sebocytes (Markovics et al, 2019). Ji found that the content of IL-1α and IL-6 in serum cytokines from patients were significantly higher than normal people (Ji et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The mitochondrial membrane potential of the HUVECs was determined by using 1,1′,3,3,3′,3′-hexamethylindodicarbocyanin iodide (DilC 1 (5)) dye. The decrease in the DilC 1 (5) intensity indicated mitochondrial depolarization, i.e., the onset of early apoptotic processes of HUVECs [ 23 , 24 ]. Cells were seeded to 96-well plates at a density of 20,000 cells per well treated with allithiamine of different concentrations (0.1, 0.5, 1, 5, 10, and 50 μg/mL).…”
Section: Methodsmentioning
confidence: 99%